2020
DOI: 10.1039/c9tb02861g
|View full text |Cite
|
Sign up to set email alerts
|

Designer DNA–silica/carbon nanotube nanocomposites for traceable and targeted drug delivery

Abstract: A programmable drug delivery system can be synthesized in a highly modular fashion from DNA-functionalized carbon nanotubes and silica nanoparticles via enzymatic rolling circle amplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Z-stack image analyses indicated that the composite materials are located inside the cells ( Supplementary Materials Figure S2a,c ). Importantly, since the composites are not cytotoxic [ 29 , 32 ], the cells were able to continue dividing, while the ingested material was evenly distributed to the daughter cells ( Figure 3 c,d; see also Supplementary Materials Video S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Z-stack image analyses indicated that the composite materials are located inside the cells ( Supplementary Materials Figure S2a,c ). Importantly, since the composites are not cytotoxic [ 29 , 32 ], the cells were able to continue dividing, while the ingested material was evenly distributed to the daughter cells ( Figure 3 c,d; see also Supplementary Materials Video S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These SiNP/CNT–DNA composites were recently developed in our group as programmable and cell-instructive biocoatings whose components and mechanical properties can be tailored by varying the concentrations of SiNP and CNT to influence the behavior of living cells [ 29 , 30 , 31 ]. In addition, these composites are readily taken up by eukaryotic cells and can thus be used for traceable and targeted drug delivery [ 32 ]. We report here for the first time the formulation of SiNP/CNT–DNA composites as bulk- and micro-formulated gels containing transcribable genetic information ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we recommend that the order of treatment should be “first cancer, second repair.” Healing is a long process, while killing process is best shortened to prevent newborn normal cells from ablation together with cancer cells and to minimize the damage to the body. Besides, by encapsulating them into micro‐ or nano‐particles, 205 the delayed release of tissue repair biomolecules or stimulating factors can be realized. Moreover, multifunctional drugs with tumor‐killing capacity and histogenesis stimulating ability might be preferred.…”
Section: Discussionmentioning
confidence: 99%
“…[21]. Hu and Niemeyer proposed a novel hydrogel material composed of silica nanoparticles, CNT and DNA fragments rich in CG/GC sequences and showed its ability to deliver DOX molecules to HeLa cells [28]. Therefore, we can conclude from that short literature review that mainly silica or gold nanoparticles are considered as 'cores' of drug carriers utilizing the folding/unfolding property of iM sequences.…”
Section: Introductionmentioning
confidence: 99%